1998
DOI: 10.1021/jo981053q
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Thioselenation of Vinylcyclopropanes with a (PhS)2−(PhSe)2 Binary System and Its Application to Thiotelluration

Abstract: A novel, highly selective method for introducing organic sulfur, selenium, and tellurium functions into vinylic cyclopropanes has been developed on the basis of the relative reactivities of organic dichalcogenides and chalcogen-centered radicals. Upon irradiation with the light of wavelength over 300 nm, the reaction of vinylcyclopropanes with diphenyl disulfide and diphenyl diselenide proceeds smoothly to provide the corresponding gamma-(selenoethyl)allylic sulfides regioselectively in good yields. Similarly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 32 publications
0
37
1
Order By: Relevance
“…Although the exact function of SELENBP1 has yet to be characterised, it is known to bind Se, 44 , 45 a trace element involved in neuroprotection. 46 , 47 , 48 , 49 , 50 , 51 It is of note that Se deficiency has been associated with higher rates of schizophrenia 52 , 53 and some studies have shown lower plasma Se concentrations in patients with schizophrenia, 54 , 55 whereas others showed that Se is unchanged in the blood and serum of patients. 56 , 57 Thus, it would be beneficial to determine the Se concentrations in CNS regions in subjects with schizophrenia to ascertain whether there is a link between Se levels and SELENBP1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact function of SELENBP1 has yet to be characterised, it is known to bind Se, 44 , 45 a trace element involved in neuroprotection. 46 , 47 , 48 , 49 , 50 , 51 It is of note that Se deficiency has been associated with higher rates of schizophrenia 52 , 53 and some studies have shown lower plasma Se concentrations in patients with schizophrenia, 54 , 55 whereas others showed that Se is unchanged in the blood and serum of patients. 56 , 57 Thus, it would be beneficial to determine the Se concentrations in CNS regions in subjects with schizophrenia to ascertain whether there is a link between Se levels and SELENBP1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Unique reactions based on the different characteristic features of disulfides and diselenides in radical reactions have already been reported, such as the thioselenation of alkynes [58], alkenes [59,60], allenes [61], enynes [58], and vinylcyclopropanes [62]. These reactions clearly demonstrate the efficacy of mixed heteroatom systems for the highly selective introduction of two (or more) heteroatom functional groups into organic molecules [55,[63][64][65].…”
Section: Perfluoroalkylchalcogenationmentioning
confidence: 77%
“…The products are formed exclusively or preferentially with the E-configuration [4]. The thiotelluration and selenotelluration of acetylenes was also described for terminal alkynes, although less efficiently [5].…”
Section: Introductionmentioning
confidence: 93%